Learned changes in outcome associability. Issue 2 (February 2019) - Quigley, Martyn C; Eatherington, Carla J; Haselgrove, Mark
When a cue reliably predicts an outcome, the associability of that cue will change. Associative theories of learning propose this change will persist even when the same cue is paired with a different outcome. These theories, however, do not extend the same privilege to an outcome; an outcome's learning history is deemed to have no bearing on subsequent new learning involving that outcome. Two experiments were conducted which sought to investigate this assumption inherent in these theories using a serial letter-prediction task. In both experiments, participants were exposed, in Stage 1, to a predictable outcome ('X') and an unpredictable outcome ('Z'). In Stage 2, participants were exposed to the same outcomes preceded by novel cues which were equally predictive of both outcomes. Both experiments revealed that participants' learning towards the previously predictable outcome was more rapid in Stage 2 than the previously unpredicted outcome. The implications of these results for theories of associative learning are discussed.